Implementation of da'wah by teachers teaching basic Islamic knowledge to converts (KFAM) in Selangor / Raba’ahadawiah Ahmad@Yunus, Ezani Yaacob and Amiratul Munirah Yahaya - Ahmad@Yunus, Raba’ahadawiah; Yaacob, Ezani; Yahaya, Amiratul Munirah (Universiti Teknologi MARA, 2022)
Teachers teaching Islamic basic education for new Muslim converts (KFAM) have important role to educate them to be pious servants of Allah, strong believers who are beneficial to the ummah. Thus, the da’wah method used by these KFAM teachers should be guided by the exemplary da’wah approaches of Rasulullah (peace be upon him). Nowadays, the state of Selangor has the highest registered number of new Muslim converts in Malaysia. This article discusses the approaches of KFAM practised by these teachers in Selangor. It also analyses the implementation of the FKAM da’wah approaches used in four districts of Selangor, namely Petaling, Gombak, Kuala Selangor and Klang. The study applied qualitative framework and the data collection method used is library research from primary and secondary sources from academic journal articles, books, working papers books which are relevant to the research's focus. Semi-structured interviews with KFAM teachers for new Muslim converts are used, while documentary analysis is applied in the study's data analysis method. The findings of the study indicate that the implementation of the da’wah approaches by the KFAM teachers for new Muslim converts are in accordance with the da’wah of Rasulullah (peace be upon him) which is suitable with the COVID-19 era. Some of these teachers applied creative and effective techniques to train new Muslim converts to be successful Muslims. In fact, this study becomes significant reference to Selangor Zakat Institution as guidance for the teachers for asnaf (zakat beneficiaries) of new Muslim converts in Selangor.